Accountability Mechanisms in Automated Decision Systems (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2025)
Accountability in automated decision systems (ADS) -- the capacity to identify responsible parties, trace decision causation, and enable meaningful redress for individuals adversely affected by algorithmic decisions -- is a foundational requirement of responsible AI governance yet remains incompletely operationalised in both technical architectures and regulatory instruments. This paper proposes a comprehensive Accountability Mechanism Framework (AMF) for ADS, comprising seven accountability mechanism classes -- traceability, auditability, explainability, contestability, human oversight, liability assignment, and redress enablement -- each specified with technical implementation requirements, organisational governance requirements, and regulatory compliance criteria. The AMF is evaluated through a mixed-methods study combining a structured assessment of 30 operational ADS across healthcare, financial services, criminal justice, public administration, and employment domains, and a survey of 94 stakeholders (affected individuals, domain experts, legal practitioners, and AI developers) on accountability mechanism adequacy. AMF assessment scores reveal that traceability (mean AMF-T = 6.8/10) and auditability (mean AMF-A = 6.4/10) are the strongest-implemented mechanisms across domains, while contestability (mean = 3.9/10) and redress enablement (mean = 3.4/10) are the weakest. Stakeholder survey results confirm a significant accountability perception gap: developers rate mechanism adequacy 2.1 points higher on average than affected individuals across all seven mechanisms (p < 0.001). The study contributes the AMF specification, a validated Accountability Adequacy Index (AAI), and a stakeholder-inclusive evaluation methodology for responsible ADS governance.